Transforming traditional lectures into a flipped classroom: an experience in a curriculum of Introduction to Clinical Medicine - Fabrizio Consorti; Valentina Mingarelli (Firenze University Press, 2018)
There is a growing pressure on the Italian academic world for a student-centered, professional competency-based education. Among the active methods, the flipped classroom is receiving more and more attention. Come trasformare un corso d'aula tradizionale in un corso flipped e perché: esperienza in un corso di Metodologia Clinica Esiste una crescente pressione sul mondo accademico italiano per una formazione centrata sullo studente, professionalizzante e orientata alla competenza. Tra i metodi attivi, la flipped classroom sta ricevendo sempre più attenzione.